Effects of three commercial vaccines against porcine parvovirus 1 in pregnant gilts. Issue 29 (29th June 2021) - Noguera, Marta; Vela, Antonio; Kraft, Christian; Chevalier, Mathieu; Goutebroze, Sylvain; de Paz, Xavier; Kunze, Marius; Rathkjen, Poul; Schacht, Erik; Garcia-Morante, Beatriz
Abstract: Porcine parvovirosis is a common and important cause of reproductive failure in naïve dams. Even though vaccination is generally effective at preventing disease occurrence, the homology between the vaccine and challenge strains has been recently suggested to play a role in protection. Therefore, the purpose of this study was to evaluate and compare the efficacy of three currently available commercial vaccines against porcine parvovirus genotype 1 (PPV1) in an experimental model using pregnant gilts. Seventy-seven PPV1-negative gilts were included in the trial and randomly allocated to four groups. In group 1, gilts received two doses, three weeks apart, of a PPV1 subunit vaccine (ReproCyc® ParvoFLEX). Following the same scheme, gilts from group 2 received two doses of a PPV1 bivalent vaccine (ERYSENG® PARVO). In group 3, gilts received two doses, four weeks apart, of a PPV1 octavalent vaccine (Porcilis® Ery + Parvo + Lepto). Lastly, gilts from group 4 were left untreated and were used as challenge controls. All gilts were artificially inseminated three weeks after completion of vaccination. Pregnant animals were subsequently challenged around 40 days of gestation with a heterologous PPV1 strain. Foetuses were harvested at around day 90 of gestation and evaluated for their macroscopic appearance (i.e., normal, mummified, or autolytic). Along the study, safety parameters after vaccination, antibody responses against PPV1 and viremia in gilts were also measured. All the foetuses in the challenge control group were mummified, which validated the challenge model, whereas the three evaluated vaccines protected the progeny against PPV1 by preventing the appearance of clinical manifestations associated to parvovirosis. Remarkably, the PPV1 subunit vaccine induced an earlier seroconversion of gilts and was the only vaccine that could prevent viremia after challenge. This vaccine also achieved the largest average litter size accompanied with a high average proportion of clinically healthy foetuses.